Analisis Implementasi Pembelajaran Abad 21 Dalam Meningkatkan Motivasi Belajar - Zohdi Halil (Mataram University, 2025)
This research aims to analyze the implementation of 21st-century skills-based learning (the 4Cs: critical thinking and problem solving, collaboration, communication, and creativity) in an effort to enhance students’ learning motivation. Using a qualitative approach with the library research method, this study reviews various recent scientific journal articles to examine the concept of 21st-century learning, learning motivation (intrinsic and extrinsic), and the relationship between the two. The results of the analysis show that 21st-century learning oriented toward a scientific approach, the utilization of information and communication technology (ICT), and differentiated learning strategies has proven effective in increasing students’ learning motivation. These approaches create a more active, relevant, and individualized learning environment, thereby generating higher engagement, a sense of ownership over the learning process, and sustained intrinsic drive. The implementation of the 4C skills also supports the transformation of students’ roles from passive objects to active subjects of learning, which ultimately has a positive impact on academic achievement and readiness to face the global challenges of the 21st century.